2022
DOI: 10.1155/2022/1208970
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Curcumin on the Inflammatory Profile of SW982 Cells in a Rheumatoid Arthritis Model

Abstract: Rheumatoid arthritis (RA) is one of the most prevalent autoimmune diseases, affecting approximately 1% of the total global population. Curcumin, a natural polyphenol is a substance that could potentially mitigate the course of this disease. To evaluate curcumin’s anti-inflammatory impact on synoviocytes in the RA model, a set of experiments was conducted on SW982 cells, stimulated by IL-1β, IL-6, or TNF-α to emulate inflammation. During the research, the curcumin effect was evaluated by measuring cell survivab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…During the development of RA, inflammation-related cytokines such as IL-1β, IL-6, or TNF-α activate FLS, transforming their phenotype into cancer-like cells known as RA-FLS cells. RA-FLS cells release cytokines, chemokines, and adhesion molecules that exacerbate auto-inflammation and contribute to joint tissue destruction [ 114 ].…”
Section: Curcumin Inflammasome and Arthritic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of RA, inflammation-related cytokines such as IL-1β, IL-6, or TNF-α activate FLS, transforming their phenotype into cancer-like cells known as RA-FLS cells. RA-FLS cells release cytokines, chemokines, and adhesion molecules that exacerbate auto-inflammation and contribute to joint tissue destruction [ 114 ].…”
Section: Curcumin Inflammasome and Arthritic Diseasesmentioning
confidence: 99%
“…Curcumin inhibited TNF-α-induced proliferation, migration, and invasion of SV-40-transformed MH7A, and fibroblast-like synoviocyte (RA-FLS) cells while also promoting cell apoptosis [ 100 , 115 ]. In another RA in vitro model, curcumin (at 10 µM) reduced the survival of synovial sarcoma SW982 cells as well as MMP1 gene expression and TNF-α protein production [ 114 ]. Wang et al [ 98 ] found that curcumin (0–10 μmol/L) also had a cytotoxic effect on mouse macrophage-like RAW 264.7 cells and could significantly inhibit the degradation of IκBα in LPS-induced RAW264.7 macrophages and in the synovium of the joints of CIA rats [ 98 ].…”
Section: Curcumin Inflammasome and Arthritic Diseasesmentioning
confidence: 99%
“…When SW982 cells stimulated with IL1β, IL6, or TNFα were used as the RA model synoviocytes, CUR was found to reduce the viability of these cells, restore the levels of MMP1 gene expression increased by stimulation with IL1β or TNFα, and decrease TNFα protein production [ 52 ]. CUR decreased the protein level of the ribosomal protein kinase P70S6K1, leading to a reduction in the activity of the cell-surviving mTOR pathway.…”
Section: Polyphenol’s Inhibitory Activity Against Mmps In Inflammator...mentioning
confidence: 99%
“…Although the original generation of FLS has advantages, it also has some disadvantages, such as limited supply, which is difficult to collect and establish. And data and a large number of studies show that human synovial sarcoma cells (SW982) and primary FLS have similar physiological and immune characteristics due to their sarcoma characteristics under inflammatory conditions, and IL-1β-stimulated SW982 cells can mimic the inflammatory state of synovial cells common in RA patients [ [26] , [27] , [28] , [29] , [30] ]. Therefore, this study chose SW982 cells as the research object and detected expression variation of inflammatory factors on the proteins and mRNA level through ELISA and real-time PCR.…”
Section: Discussionmentioning
confidence: 99%